Solid-state battery, preparation method, and electrical equipment

By setting up a modified layer of lithium fluoride in an all-solid-state battery, the problems of poor stability and large impedance between the interface between the solid electrolyte and the metal lithium negative electrode are solved, and higher battery utilization and cycle life are achieved.

CN115425276BActive Publication Date: 2025-03-18SUNWODA ELECTRONICS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211274397.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-18
Publication Date
2025-03-18
Estimated Expiration
2042-10-18

AI Technical Summary

Technical Problem

In all-solid-state batteries, the interface chemical stability between the solid electrolyte and the metal lithium negative electrode has poor interface chemical resistance, and it is easy to grow lithium dendrites on the metal surface, resulting in a reduced battery safety performance.

Method used

A modification layer is arranged between the lithium metal sheet and the solid electrolyte layer. The modification layer contains lithium fluoride. The EDS test ensures that the difference in the lithium fluoride content in different areas of the modification layer is less than or equal to 10%, the thickness of the modification layer is 2 μm to 100 μm, and the porosity is less than or equal to 10%.

Benefits of technology

By reducing the direct contact between solid electrolyte and metal lithium and reducing interface impedance, the uniformly distributed lithium fluoride in the modification layer can better induce uniform deposition of metal lithium, avoiding the growth of lithium dendrites, thereby improving the utilization rate and cycle life of solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115425276B_ABST
    Figure CN115425276B_ABST
Patent Text Reader

Abstract

The embodiment of the present invention discloses a solid-state battery and a preparation method and an electric device. The solid-state battery includes a lithium metal sheet, a solid electrolyte layer, and a modified layer arranged between the lithium metal sheet and the solid electrolyte layer, wherein the modified layer includes lithium fluoride; wherein, when two different regions of the modified layer are tested by EDS, the difference between the content of lithium fluoride in the first region and the content of lithium fluoride in the second region is less than or equal to 10%, and the lithium fluoride modified layer can reduce the direct contact between the solid electrolyte and the metallic lithium and reduce the interface impedance. At the same time, the lithium fluoride uniformly distributed in the modified layer can better induce the uniform deposition of metallic lithium and avoid the growth of lithium dendrites, thereby improving the utilization rate and cycle life of the solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a solid-state battery, a preparation method thereof, and electrical equipment. Background Art

[0002] All-solid-state battery is a battery made of high-strength solid electrolyte. Because the lithium metal anode has the lowest electrochemical potential (-3.04Vvs.SHE), low density (0.53g / cm -3 ) and a very high theoretical capacity (3860mAh g -1 ), so the use of lithium metal negative electrode in all-solid-state batteries can improve the energy density of the battery. However, because lithium metal is very active and easily reacts with other substances, and most solid electrolytes are unstable to lithium metal, a high-impedance interface layer will be formed during the battery cycle. At the same time, the solid electrolyte has poor contact with metallic lithium, and the current distribution is uneven. It is very easy to grow lithium dendrites on the metal surface. Lithium dendrites can pass through the gaps in the solid electrolyte to reach the positive electrode, which will cause the battery to short-circuit, greatly reducing the safety performance of the battery. Summary of the invention

[0003] In view of the shortcomings of the prior art, the present invention provides a solid-state battery and a preparation method and electrical equipment, aiming to solve the technical problems of poor interface chemical stability between the solid electrolyte and the metallic lithium negative electrode in the all-solid-state battery, large interface impedance, and easy growth of lithium dendrites on the metal surface.

[0004] To solve the above problems, in a first aspect, an embodiment of the present invention provides a solid-state battery, which includes a lithium metal sheet, a solid electrolyte layer, and a modification layer disposed between the lithium metal sheet and the solid electrolyte layer, wherein the modification layer includes lithium fluoride;

[0005] Wherein, when two different regions of the modified layer are tested by EDS, the difference between the content of lithium fluoride in the first region and the content of lithium fluoride in the second region is less than or equal to 10%.

[0006] Furthermore, in the solid-state battery, the difference between the content of lithium fluoride in the first region and the content of lithium fluoride in the second region is less than or equal to 5%.

[0007] Furthermore, in the solid-state battery, the thickness of the modified layer is 2 μm to 100 μm.

[0008] Furthermore, in the solid-state battery, the porosity of the modified layer is less than or equal to 10%.

[0009] Furthermore, in the solid-state battery, the lithium fluoride is in the form of one or more of flakes, particles or lines.

[0010] Furthermore, in the solid-state battery, the size of the lithium fluoride is 5nm to 500nm.

[0011] In a second aspect, an embodiment of the present invention further provides a method for preparing the solid-state battery according to the first aspect, comprising the following steps:

[0012] S1, placing the lithium metal sheet in an atmosphere of a fluoroether compound, and obtaining a surface-modified lithium metal sheet after reaction;

[0013] S2. Assembling the surface-modified lithium metal sheet with the positive electrode sheet and the solid electrolyte layer to obtain the solid-state battery.

[0014] Furthermore, in the method for preparing the solid-state battery, the molecular formula of the fluoroether compound includes C n F m H 2n-m+2 O, where m and n are natural numbers and satisfy 2≤n≤6, 1≤m≤2n.

[0015] Furthermore, in the preparation method of the solid-state battery, the reaction temperature is 80°C to 178°C, and the reaction time is 0.5h to 24h.

[0016] In a third aspect, an embodiment of the present invention further provides an electrical device, which includes the solid-state battery described in the first aspect or the solid-state battery prepared by the preparation method described in the second aspect.

[0017] By applying the technical solution of the present application, a modified layer including lithium fluoride is provided between the lithium metal sheet and the solid electrolyte layer of the solid-state battery, and the difference between the content of lithium fluoride in the first region and the content of lithium fluoride in the second region is set to be less than or equal to 10%. The lithium fluoride modified layer can reduce the direct contact between the solid electrolyte and the metallic lithium and reduce the interface impedance. At the same time, the lithium fluoride uniformly distributed in the modified layer can better induce the uniform deposition of metallic lithium and avoid the growth of lithium dendrites, thereby improving the utilization rate and cycle life of the solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying any creative work.

[0019] Figure 1 A schematic diagram of a process for preparing a solid-state battery provided by an embodiment of the present invention;

[0020] Figure 2Schematic diagram of the method for surface modification of a metallic lithium negative electrode provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] It should be understood that the term “and / or” used in the present description and the appended claims refers to and includes any and all possible combinations of one or more of the associated listed items.

[0023] As analyzed in the background technology of this application, the existing solid-state batteries, after using metallic lithium negative electrodes, will lead to defects such as poor interface chemical stability between the solid electrolyte and the metallic lithium negative electrode, large interface impedance, and easy growth of lithium dendrites on the metal surface. In order to solve the above technical problems, the present application provides a solid-state battery and its preparation method, and electrical equipment.

[0024] In one embodiment of the present application, a solid-state battery is provided, which includes a lithium metal sheet, a solid electrolyte layer, and a modification layer arranged between the lithium metal sheet and the solid electrolyte layer, wherein the modification layer includes lithium fluoride; wherein, when two different regions of the modification layer are tested using EDS (Energy Dispersive Spectrometer, electron microscope), the difference between the content of lithium fluoride in the first region and the content of lithium fluoride in the second region is less than or equal to 10%, and the areas of the first region and the second region are the same.

[0025] Specifically, the first region and the second region can be two adjacent regions in the modified layer, that is, the difference in the lithium fluoride content in the two adjacent regions of the modified layer can be less than or equal to 10%, thereby improving the uniformity of lithium fluoride distribution in the modified layer, better inducing uniform deposition of metallic lithium, and effectively inhibiting the growth of lithium dendrites, thereby improving the utilization rate and cycle life of the battery.

[0026] It can be understood that the first region and the second region in the modified layer can also be non-adjacent regions, that is, the difference in lithium fluoride content between any two regions in the modified layer is less than or equal to 10%, which can improve the uniformity of lithium fluoride distribution in the modified layer.

[0027] It can also be understood that the shape, structure and shape of lithium fluoride in the first region and the second region may be the same or different, that is, the lithium fluoride in the first region and the second region may be one or more of flaky, granular or linear shapes, but is not limited to the above shapes, and may also be other shapes or shapes similar to flaky, granular or linear shapes. The specific shape may be determined according to actual conditions and is not specifically limited in this embodiment.

[0028] It should be noted that the content of lithium fluoride in the present invention is the molar fraction of lithium fluoride.

[0029] In some embodiments, the difference in lithium fluoride content between any two regions of the modified layer is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two of the above values.

[0030] In some specific embodiments, the size of lithium fluoride in the modification layer between the lithium metal sheet and the solid electrolyte layer can be 5nm to 500nm. The size of lithium fluoride can be determined according to its specific shape. For example, when the shape of lithium fluoride in the modification layer is granular, the diameter of lithium fluoride in the modification layer can be 5nm to 500nm; when the shape of lithium fluoride in the modification layer is sheet-like or linear, the maximum length of lithium fluoride in the modification layer can be 5nm to 500nm.

[0031] In addition, the modified layer of the solid-state battery can also be divided into multiple first areas and multiple second areas, but not only divided into first areas and second areas. At the same time, the number of first areas and second areas in the modified layer can be equal or different. The specific area division and number can be selected according to the actual application, and this embodiment does not make specific limitations.

[0032] In some specific embodiments, in order to further improve the uniformity of lithium fluoride distribution in the modified layer, the difference between the lithium fluoride content in the first region and the lithium fluoride content in the second region is less than or equal to 5%, so that the lithium fluoride in the modified layer can better induce uniform deposition of metallic lithium and effectively inhibit the growth of lithium dendrites, thereby improving the utilization rate and cycle life of the battery.

[0033] In order to further effectively block the contact between the lithium metal sheet and the solid electrolyte in the solid-state battery, in some embodiments of the present application, the thickness of the modified layer between the lithium metal sheet and the solid electrolyte layer can be 2μm to 100μm, so that the interface film has good mechanical stability during the battery cycle of the solid-state battery, thereby effectively inhibiting the growth of lithium dendrites, reducing side reactions at the interface, and improving the cycle life of the solid-state battery.

[0034] In some embodiments, the thickness of the modification layer is 2 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, or a range consisting of any two of the above values.

[0035] In some embodiments, the porosity of the modified layer between the lithium metal sheet and the solid electrolyte layer can be less than or equal to 10% to increase the density of the modified layer, thereby further improving the mechanical stability of the interface film during the battery cycle of the solid-state battery, thereby effectively inhibiting the growth of lithium dendrites, reducing side reactions at the interface, and improving the cycle life of the solid-state battery.

[0036] In some embodiments, the porosity of the modified layer is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two of the above values.

[0037] It can be understood that the thickness and porosity of the modified layer between the lithium metal sheet and the solid electrolyte layer include but are not limited to the above ranges. Compared with other ranges, the limited range of the thickness and porosity of the surface modification layer of the metal lithium negative electrode in this embodiment can effectively block the contact between the lithium metal sheet and the solid electrolyte in the solid-state battery, thereby making the interface film have good mechanical stability during the cycle of the solid-state battery, thereby effectively inhibiting the growth of lithium dendrites, reducing side reactions at the interface, and improving the cycle life of the solid-state battery.

[0038] In one embodiment of the present application, Figure 1 As shown, a method for preparing a solid-state battery is provided, which comprises the following steps:

[0039] S1, placing the lithium metal sheet in an atmosphere of a fluoroether compound, and obtaining a surface-modified lithium metal sheet after reaction;

[0040] S2. Assembling the surface-modified lithium metal sheet with the positive electrode sheet and the solid electrolyte layer to obtain the solid-state battery.

[0041] Among them, the lithium metal sheet can be polished before being placed in the atmosphere of the fluorine ether compound to further improve the uniformity of the distribution of lithium fluoride in the modified layer. At the same time, the present application can use a fluorine ether compound that is liquid at room temperature to modify the surface of the lithium metal sheet, that is, the liquid fluorine ether compound is heated to a temperature such as Figure 2 The gaseous fluoroether compound shown is used to modify the surface of the lithium metal sheet to generate a modified layer between the lithium metal sheet and the solid electrolyte layer in the solid-state battery.

[0042] Typically but not limiting, the solid electrolyte includes, but is not limited to, an inorganic solid electrolyte and a polymer solid electrolyte. Among them, the inorganic solid electrolyte can be one or more of a perovskite-type non-polar solid electrolyte and a NASICON-type, and the polymer solid electrolyte can be one or more of polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, polypropylene oxide, polyvinylidene chloride, and a single-ion polymer electrolyte.

[0043] By applying the technical solution of the present application, the lithium fluoride in the surface modification layer of the prepared lithium metal sheet can be distributed more evenly and have a nanostructure, the modification layer is in closer contact with the base metal lithium, and the structure is not easily destroyed. After being applied to a solid-state battery, the direct contact between the solid electrolyte and the metal lithium can be reduced, and the interface impedance can be reduced. The lithium fluoride evenly distributed in the modification layer can better induce the uniform deposition of metal lithium. At the same time, the modification layer between the modification layer and the solid electrolyte has good chemical stability, which can resist the side reaction of the lithium metal sheet and the solid electrolyte during the battery charging and discharging process, and can effectively inhibit the growth of lithium dendrites, thereby improving the utilization rate and cycle life of the battery. In addition, the modification method is simple to operate and is easy to prepare metal lithium negative electrodes on a large scale.

[0044] In some embodiments, the specific method for surface modification of a lithium metal sheet can be: placing a polished lithium metal sheet on top of a liquid fluoroether compound at room temperature, and sealing and heating the sheet in a container so that the fluoroether compound modifies the surface of the lithium metal sheet in a vaporized state. After the reaction is completed, the sheet is cooled to room temperature to obtain a surface-modified lithium metal sheet.

[0045] In some embodiments, the thickness of the lithium metal sheet is 3 μm to 2 mm, the fluoroether compound contains a -COC- structure, and the molecular formula of the fluoroether compound can be: C n F m H 2n-m+2 O, wherein m and n are natural numbers and satisfy 2≤n≤6, 1≤m≤2n. Specifically, the fluoroether compounds mentioned in the present application may be hydrofluoroethers, which are a general term for ether compounds containing heteroatoms such as fluorine atoms in a molecule, and can generate a lithium fluoride modification layer with a stable structure in situ on the surface of a lithium metal sheet. Lithium fluoride has high mechanical strength and good stability, and can prevent the growth of dendrites and the reaction between the electrolyte and metallic lithium, thereby playing a role in stabilizing the interface. At the same time, since the number of carbon atoms in the fluoroether compounds reaches more than 6, its boiling point is relatively high, resulting in the need to use a higher temperature to gasify the fluoroether compounds, and the use of a higher temperature to gasify the fluoroether compounds is prone to decomposition of the fluoroether compounds. Therefore, in order to reduce the gasification cost of fluoroether compounds and prevent the decomposition of fluoroether compounds during heating, the number of carbon atoms in the fluoroether compounds must be not less than 2 and not more than 6, that is, 2≤n≤6.

[0046] It can be understood that n and m in the molecular formula of the fluoroether compound include the above ranges but are not limited to the above ranges. Compared with other ranges, the range provided in the present application can be used to vaporize the fluoroether compound at an appropriate temperature and smoothly modify the surface of the lithium metal sheet in the vaporized state and without decomposition, thereby making the lithium fluoride on the surface of the lithium metal sheet more evenly distributed and having a nanostructure, the modified layer is in closer contact with the base metal lithium, and the structure is not easily destroyed.

[0047] Typically, but not limiting, fluoroether compounds include, but are not limited to, one or more of 1,1,2,2-tetrafluoroethyl methyl ether, 1,1,2,2-tetrafluoroethyl ethyl ether, methyl nonafluorobutyl ether, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and the like.

[0048] In some embodiments, the reaction conditions of the lithium metal sheet in the atmosphere of the fluoroether compound can be 80°C to 178°C and 0.5h to 24h. Specifically, the fluoroether compound in the vaporized state at a temperature of 80°C to 178°C can better modify the surface of the lithium metal sheet, and after the fluoroether compound in the vaporized state modifies the surface of the lithium metal sheet for 0.5h to 24h, the volume change of the lithium metal before and after the reaction is small, the contact between the modified layer and the lithium metal sheet is closer, and the structure is not easily destroyed.

[0049] It can be understood that the reaction temperature and reaction time of the fluoroether compound for surface modification of metallic lithium in a gasified state include but are not limited to the above ranges, which are mainly determined by whether the fluoroether compound can be gasified and decomposed in the gasified state. The specific selection can be made according to the actual application, and this embodiment does not make any specific limitation.

[0050] In some embodiments, in order to ensure that the gasified fluoroether compound can fully modify the surface of the lithium metal sheet in the gasified state, the volume of the fluoroether compound accounts for 0.01% to 10% of the volume of the container, and the volume of the lithium metal sheet accounts for 0.1% to 20% of the volume of the container. Among them, the container mentioned in the present application is preferably a temperature-resistant container.

[0051] In some embodiments, the embodiments of the present application also provide an electrical device, which includes the above-mentioned solid-state battery or the solid-state battery prepared by the above-mentioned preparation method.

[0052] The electrical equipment may be, but is not limited to, electric cars, battery cars, ships, spacecraft, mobile phones, tablets, laptops, electric toys, electric tools, etc. Spacecraft may include airplanes, rockets, space shuttles, and spacecrafts; electric toys may include fixed or mobile electric toys, such as electric tank toys, game consoles, electric car toys, electric ship toys, and electric airplane toys.

[0053] The present application sets a modification layer between the lithium metal sheet and the solid electrolyte layer of the solid-state battery, and sets the difference between the lithium fluoride content in the first region and the lithium fluoride content in the second region to be less than or equal to 10%, so that the lithium fluoride modification layer can reduce the direct contact between the solid electrolyte and the metallic lithium and reduce the interface impedance. At the same time, the lithium fluoride evenly distributed in the modification layer can better induce the uniform deposition of metallic lithium and avoid the growth of lithium dendrites, thereby improving the utilization rate and cycle life of the solid-state battery.

[0054] The beneficial effects of the present application are further illustrated below in conjunction with the embodiments.

[0055] Example 1

[0056] A method for preparing a solid-state battery comprises the following steps:

[0057] S10, polishing the surface of the lithium metal sheet to a thickness of 0.5 mm and a volume of 0.04 ml;

[0058] S20, adding 1 ml of a fluoroether compound into a 50 ml sealable temperature-resistant container; wherein the fluoroether compound is 1,1,2,2-tetrafluoroethyl ethyl ether;

[0059] S30, placing the lithium metal sheet on top of the fluoroether compound at room temperature, the fluoroether compound not contacting the lithium metal sheet, and sealing the temperature-resistant container;

[0060] S40, placing the sealed heat-resistant container in an oven and heating it at 140° C. for 10 h. After the heating is completed, cooling it to room temperature, taking out the lithium metal sheet, testing the porosity of the modified layer of the lithium metal sheet, and testing the thickness of the modified layer by a focused ion beam scanning electron microscope (FIB-SEM), and testing the difference in lithium fluoride content in two different regions of the modified layer by EDS;

[0061] S50, surface modified lithium metal sheet and lithium cobalt oxide positive electrode sheet and solid electrolyte Li 10 GeP2S 12 After assembly, a solid-state battery is obtained.

[0062] Example 2

[0063] A method for preparing a solid-state battery is basically the same as that of Example 1, except that:

[0064] A sealed heat-resistant container was placed in an oven and heated at 100°C for 10 hours. After heating, it was cooled to room temperature and the lithium metal sheet was taken out. The porosity of the modified layer of the lithium metal sheet was tested. The thickness of the modified layer was tested by focused ion beam scanning electron microscopy (FIB-SEM), and the difference in lithium fluoride content in two different areas of the modified layer was tested by EDS.

[0065] Example 3

[0066] A method for preparing a solid-state battery is basically the same as that of Example 1, except that:

[0067] A sealed heat-resistant container was placed in an oven and heated at 80°C for 10 hours. After heating, it was cooled to room temperature and the lithium metal sheet was taken out. The porosity of the modified layer of the lithium metal sheet was tested. The thickness of the modified layer was tested by focused ion beam scanning electron microscopy (FIB-SEM), and the difference in lithium fluoride content in two different areas of the modified layer was tested by EDS.

[0068] Example 4

[0069] A method for preparing a solid-state battery is basically the same as that of Example 1, except that:

[0070] A sealed heat-resistant container was placed in an oven and heated at 160°C for 10 hours. After heating, it was cooled to room temperature and the lithium metal sheet was taken out. The porosity of the modified layer of the lithium metal sheet was tested. The thickness of the modified layer was tested by focused ion beam scanning electron microscopy (FIB-SEM), and the difference in lithium fluoride content in two different areas of the modified layer was tested by EDS.

[0071] Example 5

[0072] A method for preparing a solid-state battery is basically the same as that of Example 1, except that:

[0073] A sealed heat-resistant container was placed in an oven and heated at 178°C for 10 hours. After heating, it was cooled to room temperature and the lithium metal sheet was taken out. The porosity of the modified layer of the lithium metal sheet was tested. The thickness of the modified layer was tested by focused ion beam scanning electron microscopy (FIB-SEM), and the difference in lithium fluoride content in two different areas of the modified layer was tested by EDS.

[0074] Example 6

[0075] A method for preparing a solid-state battery is basically the same as that of Example 1, except that:

[0076] A sealed heat-resistant container was placed in an oven and heated at 140°C for 0.5 h. After heating, it was cooled to room temperature and the lithium metal sheet was taken out. The porosity of the modified layer of the lithium metal sheet was tested. The thickness of the modified layer was tested by focused ion beam scanning electron microscopy (FIB-SEM), and the difference in lithium fluoride content in two different areas of the modified layer was tested by EDS.

[0077] Example 7

[0078] A method for preparing a solid-state battery is basically the same as that of Example 1, except that:

[0079] A sealed heat-resistant container was placed in an oven and heated at 140°C for 5 hours. After heating, it was cooled to room temperature and the lithium metal sheet was taken out. The porosity of the modified layer of the lithium metal sheet was tested. The thickness of the modified layer was tested by focused ion beam scanning electron microscopy (FIB-SEM), and the difference in lithium fluoride content in two different areas of the modified layer was tested by EDS.

[0080] Example 8

[0081] A method for preparing a solid-state battery is basically the same as that of Example 1, except that:

[0082] A sealed heat-resistant container was placed in an oven and heated at 140°C for 16 hours. After heating, it was cooled to room temperature and the lithium metal sheet was taken out. The porosity of the modified layer of the lithium metal sheet was tested. The thickness of the modified layer was tested by focused ion beam scanning electron microscopy (FIB-SEM), and the difference in lithium fluoride content in two different areas of the modified layer was tested by EDS.

[0083] Example 9

[0084] A method for preparing a solid-state battery is basically the same as that of Example 1, except that:

[0085] A sealed heat-resistant container was placed in an oven and heated at 140°C for 24 hours. After heating, it was cooled to room temperature and the lithium metal sheet was taken out. The porosity of the modified layer of the lithium metal sheet was tested. The thickness of the modified layer was tested by focused ion beam scanning electron microscopy (FIB-SEM), and the difference in lithium fluoride content in two different areas of the modified layer was tested by EDS.

[0086] Example 10

[0087] A method for preparing a solid-state battery is basically the same as that of Example 1, except that the fluoroether compound is 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether.

[0088] Embodiment 11

[0089] A method for preparing a solid-state battery is basically the same as Example 10, except that a sealed temperature-resistant container is placed in an oven and heated at 100° C. for 10 hours. After the heating is completed, the container is cooled to room temperature, and the lithium sheet and the lithium metal sheet are taken out. The porosity of the modified layer of the lithium metal sheet is tested, and the thickness of the modified layer is tested by a focused ion beam scanning electron microscope (FIB-SEM), and the difference in lithium fluoride content in two different regions of the modified layer is tested by EDS.

[0090] Example 12

[0091] A method for preparing a solid-state battery is basically the same as Example 10, except that a sealed temperature-resistant container is placed in an oven and heated at 80° C. for 10 hours. After heating, the container is cooled to room temperature, and the lithium sheet and the lithium metal sheet are taken out. The porosity of the modified layer of the lithium metal sheet is tested, and the thickness of the modified layer is tested by a focused ion beam scanning electron microscope (FIB-SEM), and the difference in lithium fluoride content in two different regions of the modified layer is tested by EDS.

[0092] Embodiment 13

[0093] A method for preparing a solid-state battery is basically the same as Example 10, except that a sealed temperature-resistant container is placed in an oven and heated at 160° C. for 10 hours. After heating, the container is cooled to room temperature, and the lithium sheet and the lithium metal sheet are taken out. The porosity of the modified layer of the lithium metal sheet is tested, and the thickness of the modified layer is tested by a focused ion beam scanning electron microscope (FIB-SEM), and the difference in lithium fluoride content in two different regions of the modified layer is tested by EDS.

[0094] Embodiment 14

[0095] A method for preparing a solid-state battery is basically the same as Example 10, except that a sealed temperature-resistant container is placed in an oven and heated at 178° C. for 10 hours. After heating, the container is cooled to room temperature, and the lithium sheet is taken out. The lithium metal sheet is taken out, and the porosity of the modified layer of the lithium metal sheet is tested. A focused ion beam scanning electron microscope (FIB-SEM) is used to test the thickness of the modified layer, and EDS is used to test the difference in lithium fluoride content in two different regions of the modified layer.

[0096] Embodiment 15

[0097] A method for preparing a solid-state battery is basically the same as Example 10, except that a sealed temperature-resistant container is placed in an oven and heated at 140° C. for 0.5 h. After heating, the container is cooled to room temperature, and the lithium sheet and the lithium metal sheet are taken out. The porosity of the modified layer of the lithium metal sheet is tested, and the thickness of the modified layer is tested by a focused ion beam scanning electron microscope (FIB-SEM), and the difference in lithium fluoride content in two different regions of the modified layer is tested by EDS.

[0098] Example 16

[0099] A method for preparing a solid-state battery is basically the same as Example 10, except that a sealed temperature-resistant container is placed in an oven and heated at 140° C. for 5 hours. After heating, the container is cooled to room temperature, the lithium sheet is taken out, the lithium metal sheet is taken out, the porosity of the modified layer of the lithium metal sheet is tested, and the thickness of the modified layer is tested by a focused ion beam scanning electron microscope (FIB-SEM), and the difference in lithium fluoride content in two different regions of the modified layer is tested by EDS.

[0100] Embodiment 17

[0101] A method for preparing a solid-state battery is basically the same as Example 10, except that a sealed temperature-resistant container is placed in an oven and heated at 140° C. for 16 hours. After heating, the container is cooled to room temperature, the lithium metal sheet is taken out, and the porosity of the modified layer of the lithium metal sheet is tested. A focused ion beam scanning electron microscope (FIB-SEM) is used to test the thickness of the modified layer, and EDS is used to test the difference in lithium fluoride content in two different regions of the modified layer.

[0102] Embodiment 18

[0103] A method for preparing a solid-state battery is basically the same as Example 10, except that a sealed temperature-resistant container is placed in an oven and heated at 140° C. for 24 hours. After heating, the container is cooled to room temperature, the lithium metal sheet is taken out, and the porosity of the modified layer of the lithium metal sheet is tested. A focused ion beam scanning electron microscope (FIB-SEM) is used to test the thickness of the modified layer, and EDS is used to test the difference in lithium fluoride content in two different regions of the modified layer.

[0104] Comparative Example 1

[0105] A method for preparing a solid-state battery comprises the following steps:

[0106] S10, polishing the surface of the lithium metal sheet to a thickness of 0.5 mm and a volume of 0.04 ml;

[0107] S20, spraying 1 ml of 1,1,2,2-tetrafluoroethyl ethyl ether liquid on the polished lithium metal surface, letting it stand, and after the reaction is completed, wiping the liquid, drying to remove the solvent, testing the porosity of the modified layer of the lithium metal sheet, and using a focused ion beam scanning electron microscope (FIB-SEM) to test the thickness of the modified layer, and using EDS to test the difference in lithium fluoride content in two different areas of the modified layer;

[0108] S30, the surface modified lithium metal sheet and the lithium cobalt oxide positive electrode sheet and the solid electrolyte Li 10 GeP2S 12 After assembly, a solid-state battery is obtained.

[0109] Porosity test: Field emission scanning electron microscopy (FESEM) was used to obtain electron microscope images of the modified layer surface of the lithium metal sheet in Examples 1 to 18 and Comparative Example 1, and then the void distribution map in the modified layer was obtained by processing with Image J software, and the porosity of the modified layer was calculated using the membrane porosity calculation formula, and the results are shown in Table 1. The membrane porosity calculation formula is:

[0110]

[0111] Among them, A Image =ka*kb, P is the porosity, A i is the area of ​​the i-th gap in the modified layer, N is the number of gaps, A Image is the area of ​​the selected surface, a and b are the pixel values ​​of the length and width of the selected surface respectively, and k is the pixel / micron related conversion coefficient.

[0112] The solid-state batteries prepared in Examples 1 to 18 and Comparative Example 1 were charged and discharged at 0.1C, 0.33C and 0.5C rates, with a charge and discharge voltage range of 2.6V to 4.6V, and the gram capacity of the solid-state battery in the first week of charge and discharge was tested. At the same time, 100 charge and discharge cycles were performed at a 0.1C rate to test the capacity retention rate of the solid-state battery. The test results are shown in Table 1:

[0113] Table 1

[0114]

[0115]

[0116] It can be seen from Table 1 that after 100 cycles of charge and discharge at a rate of 0.1C, the capacity retention rates of the solid-state batteries provided in Examples 1 to 18 are higher than those of the comparative example. At the same time, the gram capacities in the first week of charge and discharge at rates of 0.1C, 0.33C and 0.5C are all higher than those of comparative example 1.

[0117] From the above description, it can be seen that the application of the technical solution of the present application can reduce the direct contact between the solid electrolyte and the metallic lithium and reduce the interface impedance. At the same time, the lithium fluoride evenly distributed in the modified layer can better induce the uniform deposition of metallic lithium and avoid the growth of lithium dendrites, thereby improving the utilization rate and cycle life of the solid-state battery.

[0118] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A solid-state battery, characterized in that: It comprises a lithium metal sheet, a solid electrolyte layer, and a modification layer arranged between the lithium metal sheet and the solid electrolyte layer, wherein the modification layer comprises lithium fluoride, and the lithium fluoride is obtained by placing the lithium metal sheet in an atmosphere of a fluoroether compound for reaction; Wherein, when two different regions of the modified layer are tested by EDS, the difference between the content of lithium fluoride in the first region and the content of lithium fluoride in the second region is less than or equal to 10%.

2. The solid-state battery according to claim 1, characterized in that: The difference between the content of lithium fluoride in the first region and the content of lithium fluoride in the second region is less than or equal to 5%.

3. The solid-state battery according to claim 1, characterized in that: The thickness of the modified layer is 2 μm to 100 μm.

4. The solid-state battery according to claim 1, characterized in that: The porosity of the modified layer is less than or equal to 10%.

5. The solid-state battery according to claim 1, characterized in that: The lithium fluoride is in the form of one or more of flakes, particles or lines.

6. The solid-state battery according to claim 1, characterized in that: The size of the lithium fluoride is 5nm to 500nm.

7. The method for preparing a solid-state battery according to any one of claims 1 to 6, characterized in that: The steps include: S1, placing the lithium metal sheet in an atmosphere of a fluoroether compound, and obtaining a surface-modified lithium metal sheet after reaction; S2. Assembling the surface-modified lithium metal sheet with the positive electrode sheet and the solid electrolyte layer to obtain the solid-state battery.

8. The method for preparing a solid-state battery according to claim 7, characterized in that: The molecular formula of the fluoroether compound includes C n F m H 2n-m+2 O, where m and n are natural numbers and satisfy 2≤n≤6, 1≤m≤2n.

9. The method for preparing a solid-state battery according to claim 7, characterized in that: The reaction temperature is 80° C. to 178° C., and the reaction time is 0.5 h to 24 h.

10. An electrical device, characterized in that: Including the solid-state battery described in any one of claims 1 to 6 or the solid-state battery prepared by the preparation method described in any one of claims 7 to 9.

Citation Information

Patent Citations

  • Lithium metal battery lithium negative electrode surface modification method, and lithium metal battery

    CN108448058A

  • Method for surface modification of lithium metal and application of lithium metal negative electrode

    CN109962208A

  • Protection method of lithium metal electrode

    CN110071284A

  • Nonaqueous electrolyte battery

    JP1984171462A

  • Protective layer including tin fluoride disposed on a lithium anode in a lithium-sulfur battery

    US20210359289A1